"Drama em Gente": review of George Monteiro's "The Pessoa Chronicles" - Gaspar, Frank X. (Pessoa Plural, 2017)
MONTEIRO, George (2016). The Pessoa Chronicles: Poems, 1980-2016. Willimantic: Bricktop Hill Books.